Research methods for understanding professional learning - Hall, Elaine; Wall, Kate (Bloomsbury research methods for education series, 2019)
"Practitioners are experts in their field and this book introduces research methods that help to make that expertise explicit. There is worldwide recognition of the importance of high quality, reflective practice that both engages with existing research evidence and engages in the production of new evidence. Research Methods for Understanding Professional Learning demonstrates how the knowledge about what happens in a practice context and the skills used to succeed there can be used as the building blocks for developing research methods and tools to best investigate practice. The experienced author team introduce a framework for understanding practice and for designing research about practice using a wealth of real research examples across all phases of education. This practical guide provides suggestions of a unique mix of research methods and tools, moving beyond just action research methodology, allowing the reader to engage with research design and assess how well the data gathered will answer their research question."--Back cover.